Property rights a re-examination - Penner, J. E. (James E.) (Oxford, United Kingdom New York, NY Oxford University Press, 2020)
Ranging over a host of issues, Property Rights: A Re-Examination pinpoints and addresses a number of theoretical problems at the heart of property theory. Part 1 reconsiders and refutes the bundle of rights picture of property and the related nominalist theories of property; Part 2 explores in detail the Hohfeldian theory of jural relations; Part 3 considers the form and justification of property rights, beginning with the relation an owner's liberty to use her property and her 'right to exclude', with particular reference to the tort of nuisance, anb concludes by addressing the ever-vexed question of property rights in land.
Part One. The Complex Structure of Legal Title to Property. 1. The 'Bundle of Rights' Picture of Property Revisited ; 2. Two Nominalisms: Moral-Political Nominalism and Scientific Reductionist Nominalism -- Part Two. Hohfeldian Analysis and Legal Property Rights. 3. Hohfeldian Liberties ; 4. The Problems with Powers ; 5. Multital Jural Relations ; 6. The Transmissibility of Rights and the Power to Transfer Title -- Part Three. The Form and Justification of Legal Property Rights. 7. Exclusion, Use and Usability ; 8. The Justification of Property Rights ; 9. Rights in Land -- A Conclusion of Sorts.
Includes bibliographical references (pages 211-219) and index.
Keywords: Right of property. -- Electronic book; Property -- Philosophy